2012
DOI: 10.4103/0019-5278.107075
|View full text |Cite
|
Sign up to set email alerts
|

Working condition and health hazards in beedi rollers residing in the urban slums of Mumbai

Abstract: Background:Beedi rollers are exposed to unburnt tobacco dust through cutaneous and pharyngeal route. They are not aware of their rights. Studies have been conducted on beedi workers but not many studies are carried out in urban areas. Thus, study was carried out to understand working condition and health hazards in beedi workers residing in the urban slums of Mumbai and to know whether beedi roller are in better condition in urban areas.Aim:To study working condition and health hazard in beedi rollers in the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 4 publications
1
33
0
Order By: Relevance
“…Around 75% of the women make 1000 beedi per day. (16) The study from similar area of West Bengal showed that, more than half (57.28%) started beedi rolling in the age range 15 to 25 years, nearly similar to our study. The maximum and minimum age of initiation was 50 and 6 years, respectively.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Around 75% of the women make 1000 beedi per day. (16) The study from similar area of West Bengal showed that, more than half (57.28%) started beedi rolling in the age range 15 to 25 years, nearly similar to our study. The maximum and minimum age of initiation was 50 and 6 years, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…17 Most common morbidity was weakness and fatigue followed by lower backache. 16 The prevalence of pallor reported was too less than the South India study (19.41% vs. 40%). 18 The proportion of beedi workers with high BP in a study from West Bengal was similar to current study.…”
Section: Discussionmentioning
confidence: 63%
“…The unorganized nature of work makes these occupations vulnerable to exploitative practices followed by the business owners and, as a result, the wage levels are generally much below the minimum wages prescribed by the government. [ 5 ]…”
Section: Methodsmentioning
confidence: 99%
“…Among the screened women, more than one-fifth women were bidi-workers. They have long working hours, continuous sitting work posture, exposure to tobacco dust, poor physical working conditions and non-adherence to personal protection measures (Reddy and Gupta, 2004;Sabale et al, 2012;Shukla et al, 2011;Yasmin et al, 2010;Nag et al, 2016). Evidences are emerging linking bidi-work and cervical cancer.…”
Section: Discussionmentioning
confidence: 99%